Calculation of optical and K pre-edge absorption spectra for ferrous iron of distorted sites in oxide crystals - Vercamer, Vincent; Haverkort, Maurits W. (Physical review, 2016)
Advanced semiempirical calculations have been performed to compute simultaneously optical absorption and K pre-edge x-ray absorption spectra of Fe2+ in four distinct site symmetries found in minerals. The four symmetries, i.e., a distorted octahedron, a distorted tetrahedron, a square planar site, and a trigonal bipyramidal site, are representative of the Fe2+ sites found in crystals and glasses. A particular attention has been paid to the definition of the p−d hybridization Hamiltonian which occurs for noncentrosymmetric symmetries in order to account for electric dipole transitions. For the different sites under study, an excellent agreement between calculations and experiments was found for both optical and x-ray absorption spectra, in particular in terms of relative intensities and energy positions of electronic transitions. To our knowledge, these are the first calculations of optical absorption spectra on Fe2+ placed in such diverse site symmetries, including centrosymmetric sites. The proposed theoretical model should help to interpret the features of both the optical absorption and the K pre-edge absorption spectra of 3d transition metal ions and to go beyond the usual fingerprint interpretation.